Tinjauan Hukum Atas Wanprestasi Yang Dilakukan Nasabah Dalam Perjanjian Pembiayaan Pada Perseroan Terbatas (PT) Permodalan Nasional Madani (PNM) Mekaar Syariah Unit Serangbaru 2 - Indri Yuliani; Wulan Windiarti (CV. ULIL ALBAB CORP, 2024)
The background to the writing of this thesis was a financing agreement with a Murabahah contract and a Wadiah contract entered into by PT. Madani National Capital, research that uses empirical methods to analyze legal reviews of defaults made by customers in PT financing agreements. Madani National Capital Unit Serangbaru 2. This research aims to gain a deeper understanding of cases of default that occur in sharia financing institutions. The research method used is an empirical method by collecting field data from respondents, observations, interviews who were directly involved in default and secondary data, namely books related to the discussion in this research. Discussion and analysis use qualitative analysis methods. The results of this research are that the factors that cause customers not to perform are economic factors such as a decline in the customer's financial condition, and there are also customers who deliberately do not want to fulfill their obligations. Efforts that can be made by PNM Mekaar Unit Serangbaru 2 are by means of Rescheduling, Restructuring, Reconditioning and joint responsibility.